2008
DOI: 10.1042/bj20081986
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of protein phosphatases in plants and animals

Abstract: Protein phosphorylation appears to be a universal mechanism of protein regulation. Genomics has provided the means to compile inventories of protein phosphatases across a wide selection of organisms and this has supplied insights into the evolution of this group of enzymes. Protein phosphatases evolved independently several times yielding the groups we observe today. Starting from a core catalytic domain, phosphatases evolved by a series of gene duplication events and by adopting the use of regulatory subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
207
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(216 citation statements)
references
References 91 publications
(144 reference statements)
6
207
0
3
Order By: Relevance
“…There are several morphological and functional examples of convergent evolution, such as the development of wings in birds and bats, eyes in cephalopods and mammals, and immune systems in jawed and jawless fishes (23). Some examples of convergent molecular evolution at the protein coding level have also been reported, including the origin of visual pigment genes in fishes and humans (24) and protein phosphatases in animals and plants (25). In the case reported here, a MaLR and a CORE-SINE retroposon independently evolved into functional arcuate-specific enhancers of POMC in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…There are several morphological and functional examples of convergent evolution, such as the development of wings in birds and bats, eyes in cephalopods and mammals, and immune systems in jawed and jawless fishes (23). Some examples of convergent molecular evolution at the protein coding level have also been reported, including the origin of visual pigment genes in fishes and humans (24) and protein phosphatases in animals and plants (25). In the case reported here, a MaLR and a CORE-SINE retroposon independently evolved into functional arcuate-specific enhancers of POMC in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…All three glucan phosphatases are members of the protein tyrosine phosphatase (PTP) superfamily and are classified in the heterogeneous subgroup called dual-specificity phosphatases (DSPs) that share a conserved CX 5 R catalytic motif (11,(52)(53)(54)(55)(56). Most DSPs dephosphorylate pTyr and pSer/Thr residues of proteins, while others dephosphorylate non-proteinaceous substrates such as lipids, nucleic acids, or glucans (53,54,56).…”
mentioning
confidence: 99%
“…During the 'genomic era,' an enormous number of different protein kinases and phospho-protein (P-protein) phosphatases were identified, and reversible protein phosphorylation has been shown to be involved in regulating many fundamental cellular processes. It has been reported that the combination of genes encoding protein kinases and P-protein phosphatases constitute between 2 and 4% of the total number of genes in a typical eukaryotic genome [18]. Saccharomyces cerevisiae has genes for 113 protein kinases while the Homo sapiens has 518 such genes [19].…”
Section: Introductionmentioning
confidence: 99%